2007
DOI: 10.1177/0002831207304343
|View full text |Cite
|
Sign up to set email alerts
|

Followership

Abstract: This article presents the theoretical foundation of followership. The words follower and followership are increasingly used in discussions of leadership and organizations, and many think that the field of followership began in 1988 with Kelley's “In Praise of Followers.” Followership research began in 1955, and literature in the social sciences discussed followers and followership for decades prior. By examining why leadership rather than followership is emphasized; discussing antecedents, early theory, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…As methods and theories have matured, it has become clear that followership is an underexplored area in leadership research (Lord, Brown, & Freiberg, 1999; Uhl-Bien, Riggio, Lowe, & Carsten, 2014). More recent work (Baker, 2007; Howell & Shamir, 2005) has advanced theory regarding the role of followers in aspects of leadership processes while also calling for additional empirical work in this area.…”
Section: Followership and Leader Distancementioning
confidence: 99%
“…As methods and theories have matured, it has become clear that followership is an underexplored area in leadership research (Lord, Brown, & Freiberg, 1999; Uhl-Bien, Riggio, Lowe, & Carsten, 2014). More recent work (Baker, 2007; Howell & Shamir, 2005) has advanced theory regarding the role of followers in aspects of leadership processes while also calling for additional empirical work in this area.…”
Section: Followership and Leader Distancementioning
confidence: 99%
“…Specifically, Kaiser and Craig (2011) explored the moderating role of organizational level on the relationship between seven dimensions of managerial behavior and overall leadership effectiveness, and found that behaviors associated with effectiveness differed across levels. While courage is often discussed as an important attribute of both leaders and followers (e.g., Chaleff, 1995;Baker, 2007), recent empirical studies have explored the relationship between courage and executive performance. In particular, our literature review suggests that recent empirical studies have largely focused on exploring the importance of courage for top executive performance (Sosik, Gentry, & Chun, 2012;Palanski et al, 2015).…”
Section: Behavioral Courage and Organizational Hierarchymentioning
confidence: 99%
“…That said, as early as 1988 the scholar Robert Kelley was credited for the development of the field of followership (Baker, 2007). That said, as early as 1988 the scholar Robert Kelley was credited for the development of the field of followership (Baker, 2007).…”
Section: Followershipmentioning
confidence: 99%